Supply Market Intelligence: A Managerial Handbook for Building Sourcing Strategies - Handfield, Robert (CRC Press, 2009)
Supply Market Intelligence: A Managerial Handbook for Building Sourcing Strategies charts the course to success for executives who are seeking to lead their organizations to supply-chain maturity. This volume is intended for supply-chain executives who struggle with the challenges of an uncertain supply market environment and whose supply chain function is constantly buffeted by unexpected changes in customer requirements and commodity prices.